The Influence and Significance of Contemporary Art Trends on Modernist Design - Wang, Siyu (Transactions on Social Science, Education and Humanities Research, 2023)
This paper analyzes the rise and development of art trends, analyzes the significance of contemporary art trends through art trends and the understanding of each art trend, and combines the characteristics of each school to explain the significance of contemporary art trends. By gradually analyzing the development of early art trends from point to point, and taking modernist design as the research object, the influence of contemporary art trends on modernist design is analyzed in terms of style genres and architectural design. It introduces the background of modernism and visualizes the blossoming of each artistic trend from the spiritual level to the practical level of modernist design based on specific cases.